Effects of Deficit Irrigation and Huanglongbing on Sweet Orange Trees - Silva, Jefferson Rangel da; Boaretto, Rodrigo Marcelli; Lavorenti, Jéssica Aparecida Lara; dos Santos, Bruna Castriani Ferreira; Coletta-Filho, Helvecio Della; Mattos, Dirceu (Frontiers in Plant Science, 2021)
This study addresses the interactive effects of deficit irrigation and huanglongbing (HLB) infection on the physiological, biochemical, and oxidative stress responses of sweet orange trees. We sought to answer: (i) What are the causes for the reduction in water uptake in HLB infected plants? (ii) Is the water status of plants negatively affected by HLB infection? (iii) What are the key physiological traits impaired in HLB-infected plants? and (iv) What conditions can mitigate both disease severity and physiological/biochemical impairments in HLB-infected plants? Two water management treatments were applied for 11 weeks to 1-year-old-trees that were either healthy (HLB–) or infected with HLB (+) and grown in 12-L pots. Half of the trees were fully irrigated (FI) to saturation, whereas half were deficit-irrigated (DI) using 40% of the water required to saturate the substrate. Our results demonstrated that: reduced water uptake capacity in HLB+ plants was associated with reduced root growth, leaf area, stomatal conductance, and transpiration. Leaf water potential was not negatively affected by HLB infection. HLB increased leaf respiration rates (ca. 41%) and starch synthesis, downregulated starch breakdown, blocked electron transport, improved oxidative stress, and reduced leaf photosynthesis (ca. 57%) and photorespiration (ca.57%). Deficit irrigation reduced both leaf respiration (ca. 45%) and accumulation of starch (ca.53%) by increasing maltose (ca. 20%), sucrose, glucose, and fructose contents in the leaves, decreasing bacterial population (ca. 9%) and triggering a series of protective measures against further impairments in the physiology and biochemistry of HLB-infected plants. Such results provide a more complete physiological and biochemical overview of HLB-infected plants and can guide future studies to screen genetic tolerance to HLB and improve management strategies under field orchard conditions.